Total Ecosystem Carbon Stock (TECS) in Various Tropical Forest Ecosystems of South Sorong Regency, Southwest Papua Province, Indonesia - Lense, Obed Nedjo; Wanma, Jimmy Frans; Kesaulija, Kesaulija Frenshegty; Simbiak, Fiktor; Mansyur, Fadhilah Iqra; Rachim, Armansyah K; Wanma, Beatrix; Kesaulija, Reynold; Simanjorang, Dionysius; Lense, Jane Elisabeth (Jurnal Manajemen Hutan Tropika, 2025)
The significant uncertainty concerning the role of South Sorong’s tropical forests ecosystem in the global carbon cycle is the lack of adequate data on the total carbon content of all their components. This study aimed to fill this data gap by total carbon stock in six South Sorong, Southwest Papua, and Indonesia forest ecosystems. The above-below-ground (root) carbon stock was calculated using several published allometric equations. The walkey and black and loss-on-ignition method analysed soil carbon stocks. Aboveground live c-stock ranged from 51.9 to 105.5 Mg C ha-1 and soil c-stock from 52.91 to 1,124.3 Mg C ha-1, representing the two most significant C components in all plots. The C in litter (10.5 to 49.9 Mg C ha-1), dead and downed wood (0.2 to 2.9 Mg C ha-1) and roots (9.2 to 58.2 Mg C ha-1) accounted for less than 5.3% of the total C. The total ecosystem carbon stock ranged from 213.0 to 1,217.4 Mg C ha-1. More C was found in the peat swamp forest in six forest ecosystems, where deeper soil (organic sediment) was the main support factor. Both DLFE and PSFE are unique ecosystems that need to be considered in their management so that we can benefit from those present in local, regional, and global communities.